Signal measurement and estimation techniques for micro and nanotechnology - Clevy, Cedtric; Rakotondrabe, Micky; Chaillet, Nicolas (Springer, 2011)
Signal Measurement and Estimation Techniques for Micro and Nanotechnology discusses micro, nano and robotic cells and gives a state-of-the-art presentation of the different techniques and solutions to measure and estimate signals at the micro and nano scale. New technologies and applications such as micromanipulation (artificial components, biological objects), micro-assembly (MEMS, MOEMS, NEMS) and material and surface force characterization are covered. The importance of sensing at the micro and nano scale is presented as a key issue in control systems, as well as for understanding the physical phenomena of these systems. This book also: Explains issues that make signal measurement and estimation techniques difficult at the micro-nano-scale and offers solutions. Discusses automated micro-assembly, and control of micro-nano robotic devices Presents and links signal measurement and estimation techniques for micro-nano scale systems with microfabrication methods, sensors integration and control schemes Signal Measurement and Estimation Techniques for Micro and Nanotechnology is a must-read for researchers and engineers working in MEMS and control systems